Revolusi Pembelajaran Melalui Pasti Aksi Hanifida Dalam Meningkatkan Rasa Percaya Diri Santri - Nurul Azizah Kholidasia; Jasminto Jasminto (JURNAL ILMIAH NUSANTARA, 2025)
This article discusses the learning revolution through Hanifida's actions in increasing students' self-confidence using qualitative descriptive methods with case study types. This research uses data reduction analysis and data collection using observation, interviews and documentation techniques in the field directly and checked using triangulation techniques. The results of research conducted by researchers show that: 1) The action program has been proven to increase students' self-confidence in learning. Before the students got to know this program, their learning system was still a mess. However, when the students are guided to use this program of action, the students become less lazy in studying, become fond of reading and make the students enjoy learning independently. There are 9 stages in this process, namely definitely reading, definitely understanding, definitely concluding, definitely exploring meaning, definitely summarizing, definitely drawing, definitely presenting, definitely documenting, and definitely uploading. 2). Supporting factors for the learning revolution through Hanifida's actions in increasing students' self-confidence are support from caregivers, support from parents, a supportive environment, involvement of administrators, availability of tools, materials and media, as well as predetermined regulations. Meanwhile, the inhibiting factors are accurate reading sources, monitoring control when reading, paying attention to the quality of the presentation, and students who do not yet know the true nature of the action learning model.